Umrah Celebrity Endorsement: Issues and Revised PATER Model - Binti Saupi, Norzaini; Harun, Amran; Ali, Raman; Anwer Ismael, Darbaz; Othman, Bestoon (International Journal of Psychosocial Rehabilitation, 2019)
The Umrah travel agencies offering Umrah packages are now experiencing amazing growth in Malaysia. Despite its great potential, there are various challenges faced by the Umrah travel agency that are contributing to the decline of Umrah Pilgrim demand in the year 2018. Therefore, this study aims to review the industry challenges and concerns, especially observing the role played by the religious and entertainment celebrities as spokespeople for the umrah package, which is anticipated to have an impact on the demand for umrah, specifically among generation Y. In addition, future recommendations in dealing with the consumers’ issues concerning the Umrah package and celebrity endorsement are discussed with the proposed Revised Pater Model.